2016
DOI: 10.5173/ceju.2016.596
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the adult spina bifida patient – high incidence of urologic procedures

Abstract: IntroductionTo describe the urologic outcomes of contemporary adult spina bifida patients managed in a multidisciplinary clinic.Material and methodsA retrospective chart review of patients seen in our adult spina bifida clinic from January 2004 to November 2011 was performed to identify urologic management, urologic surgeries, and co-morbidities.Results225 patients were identified (57.8% female, 42.2% male). Current median age was 30 years (IQR 27, 36) with a median age at first visit of 25 years (IQR 22, 30).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…14 Other studies have also reported a higher proportion of females in adult SB clinics, although to a lesser degree than seen in this study. 5,15,16 The greater difference seen in this cohort may be due to the lack of a transitional care process, which may disproportionally effect men. This could indicate a need to more intentionally keep men engaged in their medical care during the transitional process and in adulthood.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…14 Other studies have also reported a higher proportion of females in adult SB clinics, although to a lesser degree than seen in this study. 5,15,16 The greater difference seen in this cohort may be due to the lack of a transitional care process, which may disproportionally effect men. This could indicate a need to more intentionally keep men engaged in their medical care during the transitional process and in adulthood.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent care in the outpatient setting is thought to help these patients stay healthy and avoid potentially preventable adverse outcomes that require hospitalizations, surgeries, or emergency department visits. 25 Age-appropriate care can also help patients achieve their fullest potential as adults. 6 However, it is well-known that transitioning patients from the pediatric to adult setting can be problematic, with many patients never transitioning and others becoming lost to follow-up altogether.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that UDS is the only method for objectively assessing any abnormalities of the LUT, this technique remains underutilized. Some studies have shown that a large proportion of patients presenting with NLUTD never underwent UDS investigation in the course of their management [ 56 , 57 ]. When referred, these patients’ initial management consisted of a focused history and clinical evaluation combined with a urinalysis and PVR measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Вельтищева отмечено, что первичная диагностика нарушений мочеиспускания проводилась менее чем в 10% случаев, при этом длительность заболевания составляла более 12 месяцев. Анализ литературы также показал, что современные методы диагностики нарушений мочеиспускания, например, клиническое уродинамическое исследование (КУДИ), не использовались у пациентов с нейрогенным мочевым пузырем в ходе наблюдения и лечения, хотя КУДИ является «золотым стандартом» диагностики для категоризации нейрогенных расстройств мочеиспускания, в том числе и у детей раннего возраста [13][14][15].…”
Section:  терминология и уродинамическая классификация нейрогенного ...unclassified